AN AYURVEDIC INTERVENTION IN AMAVATA: A CASE REPORT - Das Aparajita,; Chakraborty Swagata, (International Journal of Ayurveda and Pharma Research, 2021)
Amavata is described by Madhavakara in details in the classical text Madhavanidana. We can compare Amavata with Rheumatoid Arthritis of modern science based on similar clinical features. Rheumatoid arthritis is most common chronic inflammatory disorders which affecting 0.5% Worldwide and about 0.65% to 0.75% in India. In Amavata, Ama dosha is directly involved with Vata dosha which causes joint inflammation, resulting in deformity and immobility in the fingers, feet, ankles and stiffness of the body etc. RA is managed by DMARDs and steroids but it is not completely cured by the medicines. In Ayurveda details description of management of Amavata is mentioned which includes Langhana, Swedana, Deepana, Tikta-katu rasa, Virechana, Basti etc. In this case study patient was given Udwartana, Pariseka, Matra basti, Vaitarana basti and Valuka sweda along with oral medications i.e., Amavatari rasa, Guduchi choorna with Yastimadhu choorna etc for ten days. Clinical improvement in the sign and symptoms was reported after two months which also improving the quality of life.